Use both sides of your brain - Buzan, Tony (New York, N.Y. E.P. Dutton Inc., 1983)
"Shows concrete, step-by-step exercises for discovering the powers of the long-neglected right side of the brain--while at the same time using, even more effectively, the powers of the left side."--Back cover.
You mind is better than you think -- Interconnections of the brain's neurons -- Why our performance does not match our potential -- IQ tests -- the limitations -- Reading more efficiently and faster -- Reading and learning problems -- Why reading problems exist -- Misconceptions about reading and speed reading; how they arise -- The eye -- Perception during reading and learning -- Advanced reading techniques -- Metronome training -- Memory -- Memory systems -- The number-rhyme system -- Key words and concepts in remembering -- Noting -- Key words -- Mind maps for recall and creative thinking -- Linear history of speech and print -- Advanced note taking and mapping techniques -- Mind maps -- advanced methods and uses -- Models for the brain -- Technology and new insights into ourselves: the hologram as a model for the brain -- Advanced mind mapping noting -- Wider applications of mapping techniques -- The Buzan organic study method.
"A Dutton paperback"
Includes bibliographical references (pages 152-154) and index.
Keywords: Study skills; Thought and thinking; Memory; Creative ability